Syndebukke i Gammel Testamente - Nielsen, Kirsten (Religionsvidenskabeligt Tidsskrift, 1989)
The French anthropologist René Girard is known for his theory of the unanimous victimage as the generative mechanism of all religions and social institutions. According to Girard the function of this mechanism is to stop the crisis by sacrificing one person, the scapegoat. This article gives a short introduction to Girard and discusses whether the Deuteronomistic History should be read as a hunting of scapegoats. The answer is yes, but it is shown that a great number of Old Testament texts react strongly against this cruel and arbitrary treatment of the innocent: The Book of Jonah, Gen 22, Ps 22, The Book of Job and Isa 53. In these texts the scapegoat is saved and the reader knows his innocence. Texts like these may be read as a protest against the Deuteronomistic understanding of History as a clear and righteous system, where God rewards all good and punishes all evil. And it is suggested that one of the consequences of the discovery of this victimage mechanism is that it is not only a historical, but also an ethical question whether the readers trust the historicity of texts giving words to the cries of innocent victims in the past. Trusting their suffering is the only way to do them justice today.